Religious Values in Dewa Ayu's Dance in the Adat Village of Seraya Karangasem District - Ni Putu Gatriyani (International Journal of Integrative Research, 2023)
The Hindu community in Bali, in their customs and traditions, uses dance as a form of offering and gratitude to Ida Sang Hyang Widhi Wasa . Seraya Traditional Village, Karangasem District, Karangasem Regency has a sacred dance called the Dewa Ayu Dance . The uniqueness of this dance is that the dancers are unconscious/ trance called trance . The formulation of the problem in this research is; (1) How is the procession of the Dewa Ayu dance in the Seraya Traditional Village, Karangasem District, Karangasem Regency, (2) What religious values are contained in the Dewa Ayu dance in the Seraya Traditional Village, Karangasem District, Karangasem Regency?, The purpose of this study is to analyze procession and religious values of the Dewa Ayu dance . Data analysis used descriptive methods with induction techniques and argumentation techniques, which are empirical in nature, the symptoms are natural and are re-evaluated theoretically to produce conclusions. The procession of the Dewa Ayu Dance performance begins with a prayer followed by mesapa, mendet, ngelegong and narat, and nyiratang tirta. The religious values contained in the Dewa Ayu dance include elements of religious emotion, belief systems, religious adherents, ceremonial equipment, and ceremonial system processes. Dewa Ayu dance is a guardian dance that must be preserved by increasing its existence.